2009
DOI: 10.1007/s12028-009-9252-6
|View full text |Cite
|
Sign up to set email alerts
|

Selective Immune Adsorption Treatment of Severe Guillain Barré Syndrome in the Intensive Care Unit

Abstract: In severely affected GBS patients admitted to ICU treatment with SIA seems to be safe and effective. In comparison to treatment with SIA only, sequential therapy with IVIG was not more effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 16 publications
1
11
0
7
Order By: Relevance
“…Additional experience showed that increasing the number of apheresis sessions did not correlate with further improvement of outcome (data not shown). This observation is in accord with results of IA in acute autoimmune neuropathies like Guillain-Barré Syndrome [20]. …”
Section: Discussionsupporting
confidence: 91%
“…Additional experience showed that increasing the number of apheresis sessions did not correlate with further improvement of outcome (data not shown). This observation is in accord with results of IA in acute autoimmune neuropathies like Guillain-Barré Syndrome [20]. …”
Section: Discussionsupporting
confidence: 91%
“…Like in other autoimmune neurological diseases [25,41,42] rapid recovery from life threatening crisis or acute relapses could be achieved with three to six treatments within a period of 1 to 2 weeks.…”
mentioning
confidence: 99%
“…In addition to regulatory approval, issues of reimbursement might prevent recent use of IA. In Germany, selective IA has been increasingly used in autoimmune-related neurological diseases due to its equivalent efficacy and advantageous safety profile [23]. It had been shown that IA is an effective treatment for GBS patients [23,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…In Germany, selective IA has been increasingly used in autoimmune-related neurological diseases due to its equivalent efficacy and advantageous safety profile [23]. It had been shown that IA is an effective treatment for GBS patients [23,24,25]. However, although IA therapy has been used as a treatment option for CIDP for a number of years, the efficacy of IA treatment for CIDP had not been analyzed in a larger number of patients yet, and only few case reports are found in the literature [38,39,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation